Jamaâah Rifa`iyah: From Radicalism to Indonesian Islamic Fundamentalism - Atamimi, Abdul Basit; Mulyana, Mulyana; Nurhasanah, Siti (International Journal of Islamic Khazanah, 2020)
The Rifa`iyah Jama'ah is one of the Islamic mass organizations in Indonesia founded by Kiai Ahmad Rifa` I who seems to have disappeared from circulation because of the views handed down from the days of the Dutch colonial administration, that this group or teachings were heretical and opposed to more ulama moderate against the Netherlands. The purpose of this article is to find out the movements and teachings of the Raifa`iyah Jama'ah which are considered by some to be radical, and exclusivist organizations, but over time the Rifa`iyah congregation becomes a more lenient fundamentalist organization towards the government as an effort of existence organization to be accepted by the Indonesian people in general and not be considered a radical and heretical organization by the wider community. This research is library research. This study found three main findings that the teachings and political thought of KiaiRifa'i focused on three things: first, the Dutch colonial government was Kafir, and it was haram to be followed because it was oppressing the people. Secondly, the traditional bureaucrats, including the princes and ulemas who collaborated with the Dutch, were Dutch accomplices and they were wicked. Third, the practice of religion must not be mixed with the beliefs of the ancestors, which are considered heretical and polytheistic. Of course, such teachings were considered very dangerous by the Dutch. So on May 15, 1859, he was arrested and then exiled to Ambon, Maluku. Ten years in Ambon, he was moved to Sulawesi until he died in 1869. He was buried in the Kyai Mojo tomb complex, on a hill about one km from Kampung Jawa Tondano, Minahasa, Manado, North Sulawesi.